PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THE LEARNING CELL TERHADAP MOTIVASI BELAJAR IPAS SISWA KELAS V SD INPRES 12/79 TORO KABUPATEN BONE - Kaharmita; Rosmalah; Muhammad Idris Jafar (MACCA : Science-Edu Journal, 2026)
This study aimed to determine the effect of the cooperative learning model of the The Learning Cell type on the science and social studies (IPAS) learning motivation of fifth-grade students at SD Inpres 12/79 Toro, Bone Regency. This study employed a quantitative quasi-experimental method with a Nonquivalent Control Group Design. The population of this study consisted of all fifth-grade students of SD Inpres 12/79 Toro, Bone Regency, totaling 39 students, selected using a non-probability or saturated sampling technique. The data collection technique used was a learning motivation questionnaire. The data analysis techniques employed were descriptive statistical analysis and inferential statistical analysis. The results of the study indicated that: (a) the level of learning motivation in the control class using conventional learning was in the moderate category with an average score of 54.84; (b) the level of learning motivation in the experimental class after the implementation of the cooperative learning model of the The Learning Cell type was in a higher category than the control class, with an average score of 68.30; (c) based on inferential analysis using the Independent Sample t-Test, there was a significant difference in learning motivation between students in the experimental class (VA) and the control class (VB), as indicated by the value of tcount 6.798 > ttable 2.02619, therefore the research hypothesis was accepted. It can be concluded that the cooperative learning model of the The Learning Cell type has a significant effect on the science and social studies (IPAS) learning motivation of fifth-grade students at SD Inpres 12/79 Toro, Bone Regency.